Experimental Investigation into the Control and Load Alleviation Capabilities of Articulated Winglets - A. Gatto; P. Bourdin; M. I. Friswell (International Journal of Aerospace Engineering)
An experimental investigation into the real-time flow and control characteristics of a flying wing with articulated winglets is described in this paper. The philosophy of the concept centres around the use of active, in-flight adjustment of each wing's winglet dihedral angle, both as a primary means of aircraft roll control (single winglet actuation) and though smaller equal and simultaneous winglet deflections, tailor and alleviate main wing load. Results presented in this paper do provide good evidence of the concept's ability to adequately perform both tasks, although for the current chosen wing/winglet configuration, roll control authority was unable to achieve, per unit of control surface deflection, the same level of performance set by modern aileron-based roll control methodologies.